'What would Bandit do?': reaffirming the educational role of Australian children's television during the COVID-19 pandemic and beyond. (February 2021) - Balanzategui, Jessica; Burke, Liam; McIntyre, Joanna
The COVID-19 pandemic has highlighted the multifaceted socio-cultural functions of Australian children's television. As social distancing measures forced school students to study from home, local children's TV producers and distributors contributed to home-based learning. Yet, in response to the pandemic, the Federal Government has indefinitely suspended Australian children's television quotas, the regulatory framework that sets minimum hours of local children's content for commercial television broadcasters. In response to government imposed budgetary restraints, public broadcaster, the ABC, has also made redundances in its children's content department. Such changes have occurred at a critical juncture in which the sector's long-standing contributions to the education of Australian children and pedagogy of local teachers, caregivers and parents have been brought to the fore. We argue that this pedagogical function is a core but often overlooked element of the socio-cultural value of the sector that has been highlighted during the pandemic.